Music from the ONCE Festival: 1961- 1966 - Ashley, Robert 1930-2014; Scavarda, Donald; Cacioppo, George; Reynolds, Roger; Mumma, Gordon 1935-; Wise, Bruce; Tudor, David 1926-1996; Sheff, Robert; Krumm, Philip; Crevoshay, George; Oliveros, Pauline 1932-2016; Behrman, David (New York New World Records, 2003)
Ann Arbor, Michigan, seems an unlikely site for the establishment of a major avant-garde festival that would shake the new-music community. Tucked away in America's heartland, the city is equally removed from the Eastern metropolises whose artists pride themselves on sensing the pulse of the times, and from the nonconformist West Coast. Yet during the 1960s Ann Arbor played host to one of the most extraordinary adventures in American music history: the annual ONCE Festival and its nexus of related activities. The primary aim of ONCE's founders-Robert Ashley, Gordon Mumma, George Cacioppo, Roger Reynolds, and Donald Scavarda-was to create a forum for the presentation of cutting-edge music. To this end they were phenomenally successful. Performers and composers-whether little-known or renowned-embraced the endeavor, demanding almost nothing in return. Perhaps most important, however, ONCE acted as a creative stimulus for its organizers. Scavarda describes the adventure as an explosion of pent-up energy: "Suddenly we could write anything we wanted and have it heard." And they did. The ONCE composers-and many guest artists-wrote a host of new works, some experimental, others more traditional. What united the ONCE composers was their exploration of sound, whether through the medium of extended techniques on traditional instruments, electronic (or electronically modified) timbres, or the intersection of musical sounds with those of the environment. A major slice of ONCE's rich musical legacy-35 works constituting six hours of music-is presented here, almost all for the first time. These pieces are as diverse in style as they are compelling in expression. This landmark set, the most comprehensive document ever released of this legendary event, is an opportunity for anyone interested in contemporary music to hear history in the making. Included in the set is a 140-page booklet with a lengthy scholarly essay by musicologist and biographer Leta Miller and numerous rare photos of ONCE personages and performances. Disc 1: 1961 [72:56] Robert Ashley â¬ Sonata (7:44) 2/25/61 Donald Scavarda â¬ Groups for Piano (1:03) 2/25/61 George Cacioppo â¬ String Trio (10:23) 3/4/61 Roger Reynolds â¬ Epigram and Evolution (8:50) 3/4/61 Gordon Mumma â¬ Sinfonia for 12 Instruments and Magnetic Tape (12:03) 3/4/61 Donald Scavarda â¬ In the Autumn Mountains (7:01) 3/4/61 Bruce Wise â¬ Two Pieces for Piano and Chamber Group (6:23) 3/4/61 Robert Ashley â¬ The Fourth of July (18:37) 2/25/61 Disc 2: 1962 [72:23] Donald Scavarda â¬ Matrix for Clarinetist (9:07) 6/2/62 Roger Reynolds â¬ Wedge (7:56) 2/10/62 Gordon Mumma â¬ Meanwhile, A Twopiece (7:16) 2/10/62 Donald Scavarda â¬ Sounds for Eleven (10:55) 2/16/62 Gordon Mumma â¬ From Gestures II (13:14) 2/16/62 George Cacioppo â¬ Bestiary I: Eingang (7:16) 2/16/62 Robert Ashley â¬ Details (2b) (7:09) 12/16/62 Robert Sheff (aka Blue Gene Tyranny) â¬ Ballad (8:31) 12/16/62 Disc 3: 1962â¬63 [74:21] Gordon Mumma â¬ Large Size Mograph (8:09) 12/16/62 Robert Ashley â¬ Fives (12:36) 2/9/63 Gordon Mumma â¬ A Quarter of Fourpiece (4:56) 2/9/63 George Cacioppo â¬ Two Worlds (6:02) 2/10/63 Roger Reynolds â¬ Mosaic (9:38) 2/10/63 George Cacioppo â¬ Pianopieces 1-3 (8:19) 2/16/63 Roger Reynolds â¬ A Portrait of Vanzetti (20:27) 2/16/63 Gordon Mumma â¬ Greys (3:19) 12/3/63 Stereo electronic music for the film/score Greys by Donald Scavarda Disc 4: 1963â¬1964 [76:32] Philip Krumm â¬ Music for Clocks (10:24) 2/17/63 Robert Sheff â¬ Diotima (18:58) 2/28/64 George Crevoshay â¬ 7PTPC (5:57) 2/29/64 Donald Scavarda â¬ Landscape Journey (9:31) 2/25/64 George Cacioppo â¬ Advance of the Fungi (15:54) 2/25/64 Robert Ashley â¬ in memoriam â¬¦ Crazy Horse (symphony) (15:12) 2/25/64 Disc 5: 1964â¬1966 [76:52] Bruce Wise â¬ Music for Three (29:30) 2/26/64 George Cacioppo â¬ Time on Time in Miracles (9:44) 2/12/65 David Behrman â¬ Track (10:11) 2/13/65 Pauline Oliveros â¬ Applebox Double (17:07) 3/28/66 Robert Ashley â¬ Quartet (9:51) 3/28/66
Keywords: 20th Century (1901-2000); Avant-garde; Chamber music; Keyboard music; Electronic music; USA